Bulk self-assembly and ionic conductivity of a block copolymer containing an azobenzene-based liquid crystalline polymer and a poly(ionic liquid). Issue 10 (15th February 2017) - Zhang, Yu-Dong; Ping, Jing; Wu, Qi-Wei; Pan, Hong-Bing; Fan, Xing-He; Shen, Zhihao; Zhou, Qi-Feng
Abstract : A block copolymer containing a liquid crystalline polymer and a poly(ionic liquid) self-assembles and can be used as a solid electrolyte. Abstract : By combining nitroxide-mediated block copolymerization with post functionalization and ion exchange, a series of block copolymers (BCPs) containing an azobenzene-based side-chain liquid crystalline (LC) polymer and an imidazolium-containing poly(ionic liquid) (PIL) were synthesized. The LC block of the BCPs studied herein is poly(4-[12-(4-butyl-4′-oxy-azobenzene)dodecyl]oxycarbonylstyrene) (PAzo), while the PIL block is poly(4-vinylbenzylhexylimidazoliumbis(trifluoromethanesulfonyl)imide) (PIL(TFSI)). As far as we know, this is the first series of BCPs having both PIL and LC polymer blocks. In this series of BCPs, the PIL(TFSI) blocks are totally ionized, while the polymer compositions are varied. When the weight fraction of PIL(TFSI) is 29.7%, the BCP self-assembles into a hexagonally packed cylindrical (HEX) structure. For the BCP with 56.5 wt% PIL(TFSI), it self-assembles into a lamellar (LAM) structure when the PAzo block is LC; and it changes into a HEX structure when the PAzo block enters into the isotropic state, which is attributed to the more flexible interface between PIL(TFSI) and PAzo at temperatures above the clearing temperature of PAzo. When the weight fraction of PIL(TFSI) is 65.3%, the nanostructure of the BCP remains LAM during heating. The ionic conductivities of the BCP with 65.3 wt% PIL(TFSI) at 40 and 140 °C are 4.45 × 10 −5 and 5.81 × 10 −4 S cm −1, respectively, which indicates that the BCP can be used as a solid polymer electrolyte.